2006
DOI: 10.1177/0954008306068118
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Poly(phenylene oxide-gstyrenesulfonic acid) and their Characterization for DMFC Membrane

Abstract: Well-defined poly(2,6-dimethyl-4,4 1 -phenylene oxide)-g-poly(styrenesulfonic acid) (PPO-g-PSSA) graft copolymer was synthesized via living radical polymerization. For the graft copolymer, poly(2,6-dimethylphenylene oxide) (PPO) was brominated first, and the brominated PPO (PPO-Br) was used as a macroinitiator in the atom transfer radical polymerization (ATRP) of styrenesulfonic acid sodium salt. The number of grafts per PPO chain and the molecular weight of the graft were controlled by adjusting the degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…However, the two major weight losses were observed in the SCPPO at 200 and 430 °C. These decompositions are caused by the desulfonation of sulfonic acid groups and the degradation of the PPO main chain, respectively 25, 26…”
Section: Resultsmentioning
confidence: 99%
“…However, the two major weight losses were observed in the SCPPO at 200 and 430 °C. These decompositions are caused by the desulfonation of sulfonic acid groups and the degradation of the PPO main chain, respectively 25, 26…”
Section: Resultsmentioning
confidence: 99%
“…Several groups performed reactions with bromine and they got bromination of the side chain and the arylene backbone [31][32][33]. Applying different reaction conditions, the relation of side chain bromination and backbone bromination can be influenced [34].…”
Section: Introductionmentioning
confidence: 98%
“…The former was approved by our previous study, in which the membrane directly sulfonated from BPPO (not BPPO/SPPPO blends) showed extremely low methanol permeability, especially at the case of low sulfonation degrees 35. The latter was confirmed by the job of Cho et al It was reported that membranes prepared from a brominated poly(2,6‐dimethyl‐1,4‐phenylene oxide)‐ g ‐poly(styrenesulfonic acid) (PPO‐ g ‐PSSA) graft copolymer had very low methanol permeability, with a magnitude of 10 −7 cm 2 s −1 , and this value decreased with an increase in BPPO graft 36. Though in this case, brominated PPO is used as a macro‐initiator for grafting sodium styrene sulfonated on to PPO via living free radical polymerization and increasing BPPO results in greater graft content but the resulting polymer would not contain appreciable amounts of bromine.…”
Section: Resultsmentioning
confidence: 57%